Electrophotographic toner

By using an electrophotographic toner containing a diol, dibasic acid compound and a modified siloxane, the particle size is controlled and the dispersion of siloxane is improved, and the problems of thermal shift and low-temperature fixing in the belt fixing method or the free belt clamping fixing method are solved, and excellent fixing performance is achieved.

JP7627563B2Active Publication Date: 2025-02-06KAO CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020176772
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-10-21
Publication Date
2025-02-06
Estimated Expiration
2040-10-21

AI Technical Summary

Technical Problem

The existing electrical photography toner is prone to thermal deviation when using the belt fixing method or the free belt clamping fixing method, and the low-temperature fixing performance is insufficient.

Method used

An electrophotographic toner containing a modified siloxane containing a diol and a dibasic acid compound and a modified siloxane having a hydroxy, a carboxy or an epoxy group at one or both ends is used to control the particle size of less than 6.5 μm, and a resin containing these components is used as a binder to improve the dispersion of the siloxane in the resin.

Benefits of technology

It is realized that the low-temperature fixing and thermal shift resistance are excellent in the belt fixing method or the free belt clamping fixing method, and the fixing performance is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007627563000001
    Figure 0007627563000001
  • Figure 0007627563000002
    Figure 0007627563000002
  • Figure 0007627563000003
    Figure 0007627563000003
Patent Text Reader

Abstract

To provide a toner for electrophotography that is used for an electrophotographic device using a belt fixing system or a free belt nip fixing system for a fixing device, and is excellent in low temperature fixability and hot offset resistance.SOLUTION: A toner for electrophotography includes a toner particle. The toner particle includes, as a binder resin, a resin (A) that is a reactant of an alcohol component including di- or more valent alcohol, a carboxylic acid component including di- or more valent carboxylic acid compound, and modified silicone having a hydroxy group, a carboxy group, or an epoxy group at one terminal or both terminals (where, when the modified silicone has the hydroxy group at one terminal or both terminals, the number average molecular weight of the resin (A) is 1,000 or more and 10,000 or less). The volume median particle diameter (D50) of the toner particle is 6.5 μm or less. The toner for electrophotography is used for an electrophotographic device using a belt fixing system or a free belt nip fixing system for a fixing device.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a toner for electrophotography. [Background technology]

[0002] In the field of electrophotography, with the development of electrophotographic systems, there is a demand for the development of toners for electrophotography that can meet the demands of higher image quality and higher speeds.

[0003] Patent Document 1 describes an electrophotographic toner that contains a composite polyester resin obtained by polymerizing a polyhydric alcohol, a polycarboxylic acid compound, and a silicone oil having two or more functional groups at the molecular end, and a colorant, with the aim of improving charging stability and blocking resistance. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2002-12657 A Summary of the Invention [Problem to be solved by the invention]

[0005] When the toner described in Patent Document 1 is used in an electrophotographic device that employs a belt fixing system or a free belt nip fixing system in the fixing device, the low-temperature fixing property is improved, but there are cases in which hot offset, in which the toner adheres to the fixing roll, is easily caused. One embodiment of the present invention relates to an electrophotographic toner having excellent low-temperature fixing properties and hot offset resistance, which is used in an electrophotographic apparatus using a belt fixing system or a free belt nip fixing system in a fixing device. [Means for solving the problem]

[0006] One embodiment of the present invention relates to the following [1]. [1] A toner for electrophotography comprising toner particles, the toner particles contain, as a binder resin, a resin (A) which is a reaction product of an alcohol component containing a divalent or higher alcohol, a carboxylic acid component containing a divalent or higher carboxylic acid compound, and a modified silicone having a hydroxyl group, a carboxyl group, or an epoxy group at one or both ends (however, when the modified silicone has a hydroxyl group at one or both ends, the number average molecular weight of the resin (A) is 1,000 or more and 10,000 or less); The volume median particle size (D 50 ) is 6.5 μm or less, An electrophotographic toner used in an electrophotographic apparatus using a belt fixing system or a free belt nip fixing system in a fixing device. Effect of the Invention

[0007] According to one embodiment of the present invention, it is possible to provide an electrophotographic toner having excellent low-temperature fixing properties and hot offset resistance, which is used in an electrophotographic apparatus using a belt fixing system or a free belt nip fixing system in a fixing device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] [Electrophotographic toner] The toner for electrophotography (hereinafter, also simply referred to as "toner") according to one embodiment of the present invention is an electrophotographic toner containing toner particles, the toner particles containing, as a binder resin, a resin (A) which is a reaction product of an alcohol component containing a divalent or higher alcohol, a carboxylic acid component containing a divalent or higher carboxylic acid compound, and a modified silicone having a hydroxy group, a carboxy group, or an epoxy group at one or both ends (hereinafter, also simply referred to as "modified silicone") (however, when the modified silicone has a hydroxy group at one or both ends, the number average molecular weight of the resin (A) is 1,000 or more and 10,000 or less), and the volume median particle diameter (D 50 ) is 6.5 μm or less, and is used in electrophotographic apparatuses using a belt fixing system or a free belt nip fixing system in the fixing device. According to the present invention, it is possible to provide an electrophotographic toner having excellent low-temperature fixing properties and hot offset resistance, which is used in an electrophotographic apparatus using a belt fixing system or a free belt nip fixing system in a fixing device.

[0009] Here, the belt fixing method refers to a method in which a pressure member (for example, a pressure roller) is pressed against a fixing belt to form a fixing nip portion. The free belt nip fixing method is a method in which a pressure member made up of a belt and a pad is brought into pressure contact with a fixing roll to form a fixing nip portion.

[0010] The reason why the above effect is obtained is not clear, but the following reasons are considered. First, the belt fixing method and the free belt nip fixing method have a wider nip width than the roller fixing method, and therefore more heat is transferred to the toner, improving low-temperature fixing properties. On the other hand, in the belt fixing method and the free belt nip fixing method, the nip pressure is low, so the anchor effect (penetration into media such as paper) when the toner melts is small, and hot offset resistance tends to deteriorate. Although the detailed mechanism is unknown, the inventors have conducted extensive research and found that in a toner using resin (A), the volume median particle size (D 50 It has been found that by making the above upper limit or less, it is possible to achieve both low temperature fixing property and hot offset resistance. By using resin (A) as a binder resin, which is a reaction product of an alcohol component containing a divalent or higher alcohol, a carboxylic acid component containing a divalent or higher carboxylic acid compound, and a modified silicone having a specific functional group at one end or both ends, the dispersibility of the silicone moiety in the binder resin is improved, which is considered to make it possible to improve low temperature fixing ability and hot offset resistance. On the other hand, in the belt fixing method and the free belt nip fixing method, the nip pressure is low, so the exudation of the resin (A) in the toner during melt fixing is reduced (slowed down), the peelability of the toner from the fixing member is reduced, and the hot offset resistance tends to deteriorate. However, the volume median particle size (D 50 ) to the above upper limit or less, the surface area of ​​the toner is increased, and since the surface area of ​​the toner is large even when the nip pressure is low, it is possible for the resin (A) to exude sufficiently, which is thought to improve the hot offset resistance.

[0011] The definitions of various terms used in this specification are given below. The term "carboxylic acid compound" includes not only the carboxylic acid itself, but also anhydrides that decompose during the reaction to produce an acid, and alkyl esters of each carboxylic acid (alkyl groups having 1 to 3 carbon atoms). "Bisphenol A" is 2,2-bis(4-hydroxyphenyl)propane. The term "binder resin" simply means a resin component contained in the toner, including resin (A) and resin (B) described below.

[0012] The toner used in the present invention contains toner particles, and from the viewpoint of obtaining a toner excellent in low-temperature fixing property and hot offset resistance, the toner particles contain a resin (A). The toner includes, for example, toner particles and an external additive.

[0013] [Toner Particles] The toner particles contain a resin (A). From the viewpoint of further improving low-temperature fixing property or hot offset resistance, the toner particles preferably further contain a resin (B) that does not contain a silicone-derived constituent part. The softening point of the resin (B) is preferably different from that of the resin (A) by 5° C. or more. The toner particles may further contain additives such as wax, a charge control agent, a colorant, a magnetic powder, a flowability improver, a conductivity adjuster, a reinforcing filler such as a fibrous substance, an antioxidant, an antiaging agent, and a cleaning property improver.

[0014] <Resin (A)> Resin (A) is a reaction product of an alcohol component containing a divalent or higher alcohol, a carboxylic acid component containing a divalent or higher carboxylic acid compound, and a modified silicone having a hydroxy group, a carboxy group, or an epoxy group at one or both ends, from the viewpoint of obtaining an electrophotographic toner excellent in low-temperature fixing property, hot offset resistance, storage stability, and durability (however, when the modified silicone has a hydroxy group at one or both ends, the number average molecular weight of resin (A) is 1,000 or more and 10,000 or less).

[0015] [Alcohol content] The alcohol component includes dihydric or higher alcohols. The content of the dihydric or higher alcohol in the alcohol component is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more, and 100% by mass or less. Examples of the dihydric or higher alcohol include aromatic diols, linear or branched aliphatic diols, alicyclic diols, and trihydric or higher polyhydric alcohols. Among these, aromatic diols and linear or branched aliphatic diols are preferred, and aromatic diols are more preferred.

[0016] The aromatic diol is preferably an alkylene oxide adduct of bisphenol A, more preferably represented by formula (I): [ka] (In the formula, OR 1 and R 2 O is an oxyalkylene group, and R 1 and R 2 are each independently an ethylene group or a propylene group, x and y are each an average number of moles of alkylene oxide added and are each a positive number, and the sum of x and y is 1 or more, preferably 1.5 or more, and 16 or less, preferably 8 or less, and more preferably 4 or less. Examples of the alkylene oxide adduct of bisphenol A include a propylene oxide adduct of bisphenol A and an ethylene oxide adduct of bisphenol A. One or more of these may be used. Among these, a combination of a propylene oxide adduct of bisphenol A and an ethylene oxide adduct of bisphenol A is preferred. The molar ratio of the propylene oxide adduct of bisphenol A to the ethylene oxide adduct of bisphenol A (propylene oxide adduct of bisphenol A / ethylene oxide adduct of bisphenol A) is preferably 10 / 90 or more, more preferably 15 / 85 or more, even more preferably 20 / 80 or more, and is preferably 90 / 10 or less, more preferably 70 / 30 or less, even more preferably 60 / 40 or less. When an alkylene oxide adduct of bisphenol A is contained, the amount thereof in the alcohol component is preferably 70 mol % or more, more preferably 90 mol % or more, even more preferably 95 mol % or more, and is 100 mol % or less, even more preferably 100 mol %.

[0017] As the linear or branched aliphatic diol, an aliphatic diol having a hydroxyl group bonded to a secondary carbon atom is preferred. The aliphatic diol having a hydroxyl group bonded to a secondary carbon atom preferably has 3 or more and 4 or less carbon atoms. Examples of aliphatic diols having a hydroxyl group bonded to a secondary carbon atom include 1,2-propanediol, 1,2-butanediol, 1,3-butanediol, and 2,3-butanediol. When an aliphatic diol having a hydroxyl group bonded to a secondary carbon atom is contained, the amount thereof in the alcohol component is preferably 70 mol % or more, more preferably 90 mol % or more, even more preferably 95 mol % or more, and is 100 mol % or less, even more preferably 100 mol %.

[0018] Other linear or branched aliphatic diols include, for example, ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, and 1,12-dodecanediol.

[0019] Examples of alicyclic diols include hydrogenated bisphenol A [2,2-bis(4-hydroxycyclohexyl)propane] and adducts of hydrogenated bisphenol A with alkylene oxides having 2 to 4 carbon atoms (average number of moles added: 2 to 12). Examples of trihydric or higher polyhydric alcohols include glycerin, pentaerythritol, trimethylolpropane, and sorbitol. These alcohol components may be used alone or in combination of two or more.

[0020] [Carboxylic Acid Component] The carboxylic acid component includes a divalent or higher carboxylic acid compound. The content of the divalent or higher carboxylic acid compound in the carboxylic acid component is preferably 80% by mass or more, more preferably 90% by mass or more, and further preferably 95% by mass or more, and 100% by mass or less. Examples of the divalent or higher carboxylic acid compound include aromatic dicarboxylic acid compounds, linear or branched aliphatic dicarboxylic acid compounds, alicyclic dicarboxylic acid compounds, and trivalent or higher polyvalent carboxylic acid compounds. Among these, aromatic dicarboxylic acid compounds are preferred.

[0021] Examples of aromatic dicarboxylic acid compounds include phthalic acid, isophthalic acid, and terephthalic acid. Among these, isophthalic acid and terephthalic acid are preferred, and terephthalic acid is more preferred. The amount of the aromatic dicarboxylic acid compound in the carboxylic acid component is preferably 30 mol % or more, more preferably 50 mol % or more, even more preferably 80 mol % or more, even more preferably 90 mol % or more, and 100 mol % or less.

[0022] The carbon number of the linear or branched aliphatic dicarboxylic acid compound is preferably 2 or more, more preferably 4 or more, even more preferably 8 or more, even more preferably 10 or more, and is preferably 22 or less, more preferably 16 or less. Examples of linear or branched aliphatic dicarboxylic acid compounds include oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, adipic acid, sebacic acid, dodecanedioic acid, tetradecanedioic acid, succinic acid substituted with an aliphatic hydrocarbon group having from 1 to 20 carbon atoms, or anhydrides or alkyl esters having from 1 to 3 carbon atoms. Examples of succinic acid substituted with an aliphatic hydrocarbon group having 1 to 20 carbon atoms include dodecylsuccinic acid, dodecenylsuccinic acid, and octenylsuccinic acid. Among these, succinic acid substituted with an aliphatic hydrocarbon group having 1 to 20 carbon atoms, or anhydrides thereof, are preferred. When a linear or branched aliphatic dicarboxylic acid compound is contained, the amount thereof in the carboxylic acid component is preferably 2 mol % or more, more preferably 3 mol % or more, even more preferably 5 mol % or more, and preferably 30 mol % or less, more preferably 20 mol % or less, even more preferably 10 mol % or less.

[0023] The trivalent or higher polyvalent carboxylic acid compound is preferably a trivalent carboxylic acid, such as trimellitic acid or its anhydride, of which trimellitic acid or its anhydride is preferred. When a trivalent or higher polycarboxylic acid compound is contained, the amount of the trivalent or higher polycarboxylic acid compound in the carboxylic acid component is preferably 1 mol % or more, more preferably 5 mol % or more, even more preferably 10 mol % or more, and is preferably 35 mol % or less, more preferably 30 mol % or less. These carboxylic acid compounds may be used alone or in combination.

[0024] The ratio of the carboxy groups of the carboxylic acid component to the hydroxy groups of the alcohol component (COOH groups / OH groups) is preferably 0.7 or more, more preferably 0.8 or more, and is preferably 1.3 or less, more preferably 1.2 or less.

[0025] [Modified silicone] The modified silicone used in Resin A is a modified silicone having a hydroxy group, a carboxy group, or an epoxy group at one or both ends, from the viewpoint of reacting with at least one of an alcohol component and a carboxylic acid component to obtain an electrophotographic toner having excellent low-temperature fixing properties and hot offset resistance.

[0026] More specifically, the modified silicone is preferably represented by the formula (1): [ka] [In the formula, R is independently a hydrocarbon group having 1 to 6 carbon atoms, R' is independently an alkylene group having 1 to 10 carbon atoms, R'' is independently a hydrocarbon group having 1 to 10 carbon atoms, X is independently a hydroxy group, a hydroxyalkyloxy group, a carboxy group, a carboxyalkyloxy group, an epoxy group, a glycidyl group, a glycidyloxy group, or an alicyclic epoxy group, s is an integer of 1 to 3, t is an integer of 0 to 3, and n is an integer of 5 to 300.]

[0027] The hydrocarbon group of R has 6 or less carbon atoms, preferably 5 or less, more preferably 4 or less, even more preferably 3 or less, even more preferably 2 or less, and even more preferably 1 carbon atom. Examples of the hydrocarbon group for R include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, a tert-butyl group, a pentyl group, and a phenyl group. Among these, a methyl group is preferable. The alkylene group of R' has 10 or less carbon atoms, preferably 8 or less, more preferably 5 or less, even more preferably 4 or less, even more preferably 3 or less, and preferably 1 or more, more preferably 2 or more. Examples of the alkylene group of R' include methanediyl, ethane-1,2-diyl, ethane-1,1-diyl, n-propane-1,3-diyl, n-propane-1,2-diyl, 2-methylethane-1,2-diyl, 1,4-n-butyl, 1,2-tert-butyl, and 1,5-pentyl. Among these, ethane-1,2-diyl, n-propane-1,3-diyl, and n-propane-1,2-diyl are preferred, and n-propane-1,2-diyl is more preferred. The hydrocarbon group of R'' has 10 or less, preferably 8 or less, more preferably 6 or less, even more preferably 4 or less, even more preferably 3 or less, even more preferably 2 or less, and even more preferably 1 carbon atom. Examples of the hydrocarbon group for R'' include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, a tert-butyl group, a pentyl group, and a benzyl group. X is a hydroxy group, a hydroxyalkyloxy group, a carboxy group, a carboxyalkyloxy group, an epoxy group, a glycidyl group, a glycidyloxy group, or an alicyclic epoxy group. The hydroxyalkyloxy group and the hydroxyalkyloxy group may have multiple hydroxy groups. The carboxyalkyloxy group may have multiple carboxy groups. s is 3 or less, preferably 2 or less, and more preferably 1. t is 3 or less, preferably 2 or less, and more preferably 0 or 1. n is 300 or less, preferably 200 or less, more preferably 100 or less, and even more preferably 50 or less, and is 5 or more, preferably 8 or more, and more preferably 10 or more.

[0028] The weight average molecular weight (Mw) of the modified silicone is preferably 600 or more, more preferably 800 or more, and even more preferably 1,000 or more, and is preferably 20,000 or less, more preferably 10,000 or less, more preferably 7,000 or less, more preferably 6,000 or less, more preferably 5,000 or less, and even more preferably 4,000 or less. The number average molecular weight (Mn) of the modified silicone is preferably 500 or more, more preferably 700 or more, and even more preferably 800 or more, and is preferably 10,000 or less, more preferably 5,000 or less, more preferably 4,000 or less, and even more preferably 3,000 or less.

[0029] The kinetic viscosity of the modified silicone is preferably 10 mm at 25°C. 2 / s or more, preferably 15 mm 2 / s or more, more preferably 20 mm 2 / s or more, and preferably 500 mm 2 / s or less, preferably 400 mm 2 / s or less, more preferably 300 mm 2 / s or less. The kinetic viscosity of the modified silicone is measured at 25° C. using a fully automatic micro dynamic viscometer (manufactured by Viscotec Co., Ltd.).

[0030] The functional group equivalent of the modified silicone is preferably 10 g / mol or more, more preferably 100 g / mol or more, even more preferably 200 g / mol or more, and is preferably 5,000 g / mol or less, more preferably 4,000 g / mol or less, even more preferably 3,000 g / mol or less. The functional group equivalent weight means the mass of the modified silicone per mole of functional group.

[0031] As the modified silicone used in resin A, from the viewpoint of obtaining a toner having excellent storage stability, a modified silicone (a) having a hydroxy group at one or both ends (hereinafter, simply referred to as "modified silicone (a)") is preferable. That is, the modified silicone (a) is preferably represented by the formula (1a): [ka] [In the formula, R, R', R'', s, t and n are defined as in the above formula (1). X 1 each independently represents a hydroxy group or a hydroxyalkyloxy group. The hydroxyalkyloxy group may have a plurality of hydroxy groups. The number of carbon atoms in the hydroxyalkyl group is preferably 10 or less, more preferably 8 or less, and even more preferably 6 or less. R'X 1 Examples of the group represented by the formula include the following substituents 2a-1 to 2a-3. Among these, the substituent 2a-1 or the substituent 2a-2 is preferred, and the substituent 2a-1 is more preferred. * is a bonding site with Si. [ka]

[0032] From the viewpoint of further improving storage stability, the modified silicone (a) preferably has hydroxy groups at both ends. That is, from the viewpoint of further improving storage stability, the modified silicone (a) preferably has hydroxy groups at both ends, R'X 1 That is, in the above formula (1a), s and t are 1. Examples of modified silicones (a) include silicones modified with carbinol at both ends (commercially available products include, for example, "X-22-160AS", "KF-6000", "KF-6001", "KF-6002", and "KF-6003" (all manufactured by Shin-Etsu Chemical Co., Ltd.)), and silicones modified with carbinol at one end (commercially available products include, for example, "X-22-170BX", "X-22-170DX", "X-22-176DX", and "X-22-176GX-A" (all manufactured by Shin-Etsu Chemical Co., Ltd.)).

[0033] The modified silicone used in the resin A is preferably a modified silicone (b) having an epoxy group at one or both ends, from the viewpoint of obtaining a toner having excellent durability. In other words, the modified silicone (b) is Preferably, the compound of formula (1b): [ka] [In the formula, R, R', R'', s, t and n are defined as in the above formula (1). X 2 each independently represents an epoxy group, a glycidyl group, a glycidyloxy group, or an alicyclic epoxy group. R'X 2 Examples of the group represented by the formula: embedded image include the following substituents 2b-1 to 2b-3. Among these, the substituent 2b-1 is preferred. [ka]

[0034] From the viewpoint of further improving low-temperature fixing ability and hot offset resistance, it is preferable that the modified silicone (b) has an epoxy group at one end. That is, from the viewpoint of further improving low-temperature fixing ability and hot offset resistance, the modified silicone (b) has an epoxy group at one end. 2 That is, in the above formula (1b), s is 1 and t is 0. From the viewpoint of further improving durability, the modified silicone (b) preferably has epoxy groups at both ends. That is, from the viewpoint of further improving durability, the modified silicone (b) preferably has R'X 2 That is, in the above formula (1b), s and t are 1. Examples of modified silicones (b) include silicones modified with epoxy at both ends (commercially available products include "KF-105", "X-22-163A", "X-22-163B", "X-22-163C", "X-22-169AS", and "X-22-169B" (all manufactured by Shin-Etsu Chemical Co., Ltd.)), and silicones modified with epoxy at one end (commercially available products include "X-22-173BX" and "X-22-173DX" (all manufactured by Shin-Etsu Chemical Co., Ltd.)).

[0035] The modified silicone used in the resin A is preferably a modified silicone (c) having a carboxy group at one or both ends, from the viewpoint of obtaining a toner having excellent durability. That is, the modified silicone (c) is preferably represented by the formula (1c): [ka] [In the formula, R, R', R'', s, t and n are defined as in the above formula (1). X 3 each independently represents a carboxy group or a carboxyalkyloxy group. R'X 3 Examples of the group represented by the formula: [ka]

[0036] From the viewpoint of further improving the low-temperature fixing property and hot offset resistance, the modified silicone (c) preferably has a carboxyl group at both ends. That is, from the viewpoint of further improving the low-temperature fixing property and hot offset resistance, the modified silicone (c) preferably has a carboxyl group at both ends. 3 That is, in the above formula (1c), s and t are 1. Examples of modified silicones (c) include silicones modified with carboxyl groups at both ends (commercially available products include "X-22-162C" and "BY16-750" (manufactured by Shin-Etsu Chemical Co., Ltd.)) and silicones modified with a carboxyl group at one end (commercially available product includes "X-22-3710" (manufactured by Shin-Etsu Chemical Co., Ltd.)).

[0037] In the raw materials for resin (A), the amount of modified silicone is, from the viewpoints of low-temperature fixability and hot offset resistance, preferably 0.1 mass % or more, more preferably 1 mass % or more, even more preferably 2 mass % or more, even more preferably 4 mass % or more, and is preferably 9 mass % or less, more preferably 7 mass % or less, even more preferably 6 mass % or less, based on the total amount of the alcohol component, the carboxylic acid component and the modified silicone.

[0038] In the raw materials for resin (A), the total amount of the alcohol component and the carboxylic acid component, based on the total amount of the alcohol component, the carboxylic acid component and the modified silicone, is preferably 91 mass% or more, more preferably 93 mass% or more, even more preferably 94 mass% or more, and is preferably 99.9 mass% or less, more preferably 99 mass% or less, even more preferably 98 mass% or less.

[0039] The above amounts are calculated based on the alcohol component, the carboxylic acid component and the modified silicone, and do not take into account the amount of water removed by condensation. In addition, when the modified silicone has a hydroxy group or a carboxy group, it can also be understood as an alcohol component or a carboxylic acid component, but when the compound having a hydroxy group or a carboxy group contains a silicone skeleton, it is considered to be a modified silicone. For example, when calculating the total amount of the alcohol component and the carboxylic acid component, the modified silicone having a hydroxy group or a carboxy group is not included in these total amounts.

[0040] [Physical properties of resin (A)] The number average molecular weight of the resin (A) is preferably 800 or more, and from the viewpoint of obtaining excellent hot offset resistance, it is more preferably 1,500 or more, and even more preferably 2,500 or more, and is preferably 30,000 or less, more preferably 20,000 or less, and from the viewpoint of obtaining excellent low-temperature fixing property, it is more preferably 10,000 or less, more preferably 5,000 or less, and even more preferably 4,000 or less. However, when the modified silicone of resin (A) is a modified silicone having a hydroxy group at one end or both ends, from the viewpoint of obtaining excellent hot offset resistance, the number average molecular weight of resin (A) is 1,000 or more, preferably 1,500 or more, more preferably 2,000 or more, and even more preferably 2,500 or more, and from the viewpoint of obtaining excellent low-temperature fixing property, it is 10,000 or less, preferably 8,000 or less, more preferably 6,000 or less, even more preferably 5,000 or less, and even more preferably 4,000 or less.

[0041] The acid value of the resin (A) is preferably 0.1 mgKOH / g or more, more preferably 0.5 mgKOH / g or more, even more preferably 1 mgKOH / g or more, and is preferably 40 mgKOH / g or less, more preferably 30 mgKOH / g or less, even more preferably 20 mgKOH / g or less.

[0042] From the viewpoint of further improving hot offset resistance and storage stability, the softening point of the resin (A) is preferably 70° C. or higher, more preferably 90° C. or higher, and even more preferably 100° C. or higher, and from the viewpoint of further improving low-temperature fixability, it is preferably 140° C. or lower, more preferably 130° C. or lower, even more preferably 120° C. or lower, and even more preferably 110° C. or lower.

[0043] The glass transition temperature of the resin (A) is preferably 45° C. or higher, more preferably 50° C. or higher, and even more preferably 55° C. or higher, from the viewpoint of further improving hot offset resistance and storage stability, and is preferably 80° C. or lower, more preferably 70° C. or lower, and even more preferably 65° C. or lower, from the viewpoint of further improving low-temperature fixability.

[0044] The number average molecular weight, acid value, softening point, and glass transition temperature of the resin (A) can be appropriately adjusted by the types and amounts of raw material monomers used, as well as production conditions such as reaction temperature, reaction time, and cooling rate, and these values ​​can be determined by the methods described in the examples. When two or more resins (A) are used in combination, the number average molecular weight, acid value, hydroxyl value, softening point and glass transition temperature of the mixture are preferably within the above-mentioned ranges.

[0045] [Method for producing resin (A)] Resin (A) can be obtained, for example, by reacting an alcohol component, a carboxylic acid component, and a modified silicone. In this reaction, if necessary, an esterification catalyst such as tin(II) di(2-ethylhexanoate), dibutyltin oxide, or titanium diisopropylate bistriethanolamine may be used in an amount of 0.01 to 5 parts by mass per 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component, or an esterification promoter such as gallic acid (same as 3,4,5-trihydroxybenzoic acid) may be used in an amount of 0.001 to 0.5 parts by mass per 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component. The reaction temperature is preferably 120° C. or higher, more preferably 160° C. or higher, even more preferably 180° C. or higher, and is preferably 250° C. or lower, more preferably 240° C. or lower. The reaction may be carried out in an inert gas atmosphere.

[0046] From the viewpoint of further improving the low-temperature fixing property and hot offset resistance of the toner, the content of the resin (A) in the binder resin of the toner is preferably 10% by mass or more, more preferably 20% by mass or more, even more preferably 30% by mass or more, even more preferably 40% by mass or more, even more preferably 50% by mass or more, and is 100% by mass or less, preferably 90% by mass or less, more preferably 80% by mass or less, even more preferably 70% by mass or less.

[0047] <Resin (B)> The resin (B) is preferably a polycondensate of an alcohol component and a carboxylic acid component, and more preferably a polyester resin. However, this does not include the case of the above resin (A). In other words, the resin (B) does not contain a silicone-derived structural portion. The alcohol component and the carboxylic acid component are as exemplified above.

[0048] [Physical properties of resin (B)] The acid value of the resin (B) is preferably 0.1 mgKOH / g or more, more preferably 0.5 mgKOH / g or more, even more preferably 1 mgKOH / g or more, and is preferably 40 mgKOH / g or less, more preferably 30 mgKOH / g or less, even more preferably 20 mgKOH / g or less.

[0049] The difference between the softening point of resin (B) and that of resin (A) is preferably 5° C. or more, more preferably 10° C. or more, even more preferably 20° C. or more, even more preferably 30° C. or more, and is preferably 60° C. or less, more preferably 50° C. or less, even more preferably 40° C. or less. The softening point of resin (B) is preferably higher than the softening point of resin (A). From the viewpoint of further improving hot offset resistance and storage stability, the softening point of the resin (B) is preferably 70° C. or higher, more preferably 90° C. or higher, even more preferably 100° C. or higher, and even more preferably 110° C. or higher. From the viewpoint of further improving hot offset resistance and storage stability, the softening point of resin (B) is preferably 160°C or less, more preferably 150°C or less, even more preferably 140°C or less, even more preferably 130°C or less, and even more preferably 125°C or less.

[0050] The glass transition temperature of resin (B) is preferably 50°C or higher, more preferably 60°C or higher, even more preferably 63°C or higher, and preferably 80°C or lower, more preferably 75°C or lower, even more preferably 70°C or lower.

[0051] The acid value, softening point, and glass transition temperature of the resin (B) can be appropriately adjusted by the types and amounts of raw material monomers used, as well as production conditions such as reaction temperature, reaction time, and cooling rate, and these values ​​can be determined by the methods described in the examples. When two or more kinds of resins (B) are used in combination, it is preferable that the acid value, softening point and glass transition temperature of the mixture are each within the above-mentioned ranges.

[0052] Resin (B) can be obtained, for example, by polycondensation of an alcohol component and a carboxylic acid component. The polycondensation conditions can be the same as those shown in the above-mentioned method for producing resin (A).

[0053] When resin (B) is contained and the softening point of resin (B) is higher than the softening point of resin (A), the mass ratio of resin (A) to resin (B) [resin (A) / resin (B)] is, from the viewpoint of improving low-temperature fixing ability and hot offset resistance, preferably 20 / 80 or more, more preferably 30 / 70 or more, even more preferably 40 / 60 or more, even more preferably 50 / 50 or more, and is preferably 90 / 10 or less, more preferably 80 / 20 or less. Furthermore, when resin (B) is contained and the softening point of resin (B) is lower than the softening point of resin (A), the mass ratio of resin (A) to resin (B) [resin (A) / resin (B)], from the viewpoint of improving low-temperature fixing ability and hot offset resistance, is preferably 10 / 90 or more, more preferably 20 / 80 or more, and is preferably 80 / 20 or less, more preferably 70 / 30 or less, even more preferably 60 / 40 or less, and even more preferably 50 / 50 or less.

[0054] When resin (B) is contained and the softening point of resin (B) is higher than the softening point of resin (A), the content of resin (B) in the binder resin of the toner is, from the viewpoint of improving low-temperature fixing property and hot offset resistance, preferably 10% by mass or more, more preferably 20% by mass or more, even more preferably 30% by mass or more, and preferably 90% by mass or less, more preferably 80% by mass or less, even more preferably 70% by mass or less, even more preferably 60% by mass or less, and even more preferably 50% by mass or less. Furthermore, when resin (B) is contained and the softening point of resin (B) is lower than the softening point of resin (A), the content of resin (B) in the binder resin of the toner is, from the viewpoint of improving low-temperature fixing property and hot offset resistance, preferably 10% by mass or more, more preferably 20% by mass or more, even more preferably 30% by mass or more, even more preferably 40% by mass or more, even more preferably 50% by mass or more, and preferably 90% by mass or less, more preferably 80% by mass or less, even more preferably 70% by mass or less.

[0055] <Wax> Examples of the wax include hydrocarbon waxes, ester waxes, silicone waxes, and fatty acid amide waxes.

[0056] The melting point of the wax is preferably 60° C. or higher, more preferably 70° C. or higher, and preferably 160° C. or lower, more preferably 150° C. or lower, and even more preferably 140° C. or lower. When two or more waxes are used in combination, it is preferable that the melting point of each wax is within the above-mentioned range. Since the resin (A) has excellent releasability, the toner does not need to contain wax. The wax content is preferably 1 part by mass or less, more preferably 0.5 parts by mass or less, and even more preferably 0.1 parts by mass or less, and is preferably 0 part by mass or more, relative to 100 parts by mass of the total amount of the binder resin.

[0057] <Charge control agent> The charge control agent may contain either a positively chargeable charge control agent or a negatively chargeable charge control agent. Examples of the positively charged charge control agent include nigrosine dyes such as "Nigrosine Base EX", "Oil Black BS", "Oil Black SO", "Bontron N-01", "Bontron N-04", "Bontron N-07", "Bontron N-09", and "Bontron N-11" (all manufactured by Orient Chemical Industry Co., Ltd.); triphenylmethane dyes containing tertiary amines as side chains, quaternary ammonium salt compounds such as "Bontron P-51" (manufactured by Orient Chemical Industry Co., Ltd.), cetyltrimethylammonium bromide, and "COPY CHARGE PX VP435" (manufactured by Clariant); polyamine resins such as "AFP-B" (manufactured by Orient Chemical Industry Co., Ltd.); imidazole derivatives such as "PLZ-2001" and "PLZ-8001" (all manufactured by Shikoku Chemical Industry Co., Ltd.); and styrene-acrylic resins such as "FCA-701PT" (manufactured by Fujikura Chemical Industry Co., Ltd.).

[0058] Examples of negatively chargeable charge control agents include metal-containing azo dyes such as "Varifast Black 3804", "Bontron S-31", "Bontron S-32", "Bontron S-34", and "Bontron S-36" (all manufactured by Orient Chemical Industry Co., Ltd.), "Aizen Spiron Black TRH", and "T-77" (manufactured by Hodogaya Chemical Industry Co., Ltd.); metal compounds of benzilic acid compounds such as "LR-147" and "LR-297" (both manufactured by Nippon Carlit Co., Ltd.); metal compounds of salicylic acid compounds such as "Bontron E-81", "Bontron E-84", "Bontron E-88", and "Bontron E-304" (all manufactured by Orient Chemical Industry Co., Ltd.), and "TN-105" (manufactured by Hodogaya Chemical Industry Co., Ltd.); copper phthalocyanine dyes; quaternary ammonium salts such as "COPY CHARGE NX VP434" (manufactured by Clariant), nitroimidazole derivatives, and organometallic compounds. Among the charge control agents, negatively chargeable charge control agents are preferred, and metal compounds of benzilic acid compounds are more preferred.

[0059] The content of the charge control agent is preferably 0.01 parts by mass or more, more preferably 0.2 parts by mass or more, and preferably 10 parts by mass or less, more preferably 5 parts by mass or less, even more preferably 3 parts by mass or less, and even more preferably 2 parts by mass or less, relative to 100 parts by mass of the total amount of the binder resin.

[0060] <Coloring agent> As the colorant, any of the dyes, pigments, etc. used as colorants for toners can be used, such as carbon black, phthalocyanine blue, permanent brown FG, brilliant fast scarlet, pigment green B, rhodamine B base, solvent red 49, solvent red 146, solvent blue 35, quinacridone, carmine 6B, disazo yellow, etc. can be used, and the toner of the present invention may be either a black toner or another color toner.

[0061] From the viewpoint of improving the image density of the toner, the content of the colorant is preferably 0.3 parts by mass or more, more preferably 0.5 parts by mass or more, and is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, and even more preferably 5 parts by mass or less, relative to 100 parts by mass of the total amount of the binder resin.

[0062] [Toner manufacturing method] The toner may be obtained by any known method such as a melt-kneading method, an emulsion phase inversion method, a polymerization method, or an emulsion aggregation method. From the viewpoints of productivity and dispersibility of the colorant, however, a pulverized toner obtained by a melt-kneading method is preferred. In the case of a pulverized toner by a melt kneading method, for example, raw materials such as resin (A), resin (B), wax, charge control agent, colorant, etc. are uniformly mixed in a mixer such as a Henschel mixer, and then melt-kneaded in an internal kneader, a single-screw or twin-screw extruder, an open roll type kneader, etc., and then cooled, pulverized, and classified to produce the toner. The toner production method preferably includes a step of melt-kneading a mixture containing the resin (A) at a temperature in the range of 80° C. or more and 160° C. or less. The melt-kneading temperature is preferably 80° C. or more, more preferably 90° C. or more, and preferably 160° C. or less, more preferably 150° C. or less. The toner production method preferably includes a step of pulverizing and classifying the mixture obtained by melt kneading to obtain toner particles. The pulverization and classification can be performed by a known method.

[0063] The volume median particle size of toner particles (D 50 From the viewpoint of obtaining a high-quality image, the thickness is preferably 2 μm or more, more preferably 3 μm or more, and even more preferably 4 μm or more, and from the viewpoint of hot offset resistance, the thickness is 6.5 μm or less, preferably 6 μm or less, and more preferably 5.8 μm or less.

[0064] The toner is preferably treated by adding a fluidizing agent or the like as an external additive to the surface of the toner particles. Examples of the external additive include inorganic material particles such as hydrophobic silica, titanium oxide particles, alumina particles, cerium oxide particles, and carbon black, and polymer particles such as polycarbonate, polymethyl methacrylate, and silicone resin. Among these, hydrophobic silica is preferred. When an external additive is used, the amount of the external additive added is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, and preferably 5 parts by mass or less, more preferably 4 parts by mass or less, and even more preferably 3 parts by mass or less, relative to 100 parts by mass of the toner particles.

[0065] Toners are used, for example, to develop latent images formed in electrophotography, electrostatic recording, electrostatic printing, etc. Toners can be used as one-component developers, or mixed with a carrier to form two-component developers. EXAMPLES

[0066] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. Physical properties of resins and the like were measured by the following methods. In the notation "alkylene oxide (X)" and the like, the number X in parentheses means the average number of moles of alkylene oxide added.

[0067] [Measurement method] [Kinematic Viscosity of Modified Silicone] The kinetic viscosity of the modified silicone was determined using the catalog value for each product.

[0068] [Functional Group Equivalent of Modified Silicone] The functional group equivalent weight of the modified silicone was taken from the catalog value of each product.

[0069] [Softening point of resin] Using a flow tester "CFT-500D" (Shimadzu Corporation), 1g of sample is heated at a temperature increase rate of 6℃ / min while applying a load of 1.96MPa with the plunger, and extruding the sample from a nozzle with a diameter of 1mm and a length of 1mm. The plunger descent amount of the flow tester is plotted against the temperature, and the temperature at which half of the sample flows out is taken as the softening point.

[0070] [Glass transition temperature of resin] Using a differential scanning calorimeter "Q100" (manufactured by TA Instruments Japan Co., Ltd.), 0.02 g of the sample was weighed into an aluminum pan, heated to 200°C, and cooled to 0°C at a rate of 10°C / min. The sample was then heated at a rate of 10°C / min and the calorific value was measured. The temperature of the peak with the largest peak area among the observed endothermic peaks was taken as the maximum endothermic peak temperature. In the case of an amorphous resin, when a peak is observed, the temperature of the peak is taken as the glass transition temperature. When no peak is observed but a step is observed, the temperature at the intersection of the tangent showing the maximum slope of the curve at the step and an extension of the baseline on the low temperature side of the step is taken as the glass transition temperature.

[0071] [Acid value of resin] The acid value of the resin is measured according to the neutralization titration method described in JIS K 0070: 1992. However, the acid value is measured using a mixed solvent of acetone and toluene [acetone:toluene=1:1 (volume ratio)].

[0072] [Number average molecular weight and weight average molecular weight of resin and modified silicone] The molecular weight distribution is measured by gel permeation chromatography (GPC) according to the following method, and the number average molecular weight and weight average molecular weight are determined. (1) Preparation of sample solution The sample is dissolved in tetrahydrofuran at 25° C. so that the concentration becomes 0.5 g / 100 mL. Next, this solution is filtered using a fluororesin filter "DISMIC-25JP" (manufactured by Advantec Toyo Co., Ltd.) with a pore size of 0.2 μm to remove undissolved components, and a sample solution is obtained. (2) Molecular weight measurement The following measuring equipment and analytical column are used, tetrahydrofuran is used as the eluent at a flow rate of 1 mL per minute, and the column is stabilized in a thermostatic bath at 40°C. 100 μL of the sample solution is injected into the column for measurement. The molecular weight of the sample is calculated based on a calibration curve that has been prepared in advance. The calibration curve used here includes several types of monodisperse polystyrene "A-500" (5.0 x 10 2 ), "A-1000" (1.01 x 10 3 ), "A-2500" (2.63×10 3 ), "A-5000" (5.97 x 10 3 ), "F-1" (1.02 x 10 4 ), "F-2" (1.81 x 10 4 ), "F-4" (3.97 x 10 4 ), "F-10" (9.64×10 4 ), "F-20" (1.90×10 5 ), "F-40" (4.27×10 5 ), "F-80" (7.06×10 5 ), "F-128" (1.09×10 6 ) (all manufactured by Tosoh Corporation) are used as standard samples. Measuring device: "HLC-8220GPC" (Tosoh Corporation) Analytical column: "GMHXL" + "G3000HXL" (both manufactured by Tosoh Corporation)

[0073] [Average particle size of external additives] The average particle size refers to the number-average particle size, and is the number-average value of the particle sizes of 500 particles measured from a scanning electron microscope (SEM) photograph of the external additive. When a particle has a major axis and a minor axis, the particle size refers to the major axis.

[0074] [Volume Median Particle Size of Toner] The volume median particle size of toner particles (D 50 ) is measured as follows: Measuring device: "Coulter Multisizer II" (manufactured by Beckman Coulter, Inc.) Aperture diameter: 50μm Analysis software: "Coulter Multisizer AccuComp Version 1.19" (Beckman Coulter, Inc.) Electrolyte: "Isoton II" (Beckman Coulter, Inc.) Dispersion: Emulgen "109P" (Kao Corporation, polyoxyethylene lauryl ether, HLB (Griffin): 13.6) was dissolved in the electrolyte to obtain a dispersion with a concentration of 5% by mass. Dispersion conditions: 10 mg of the measurement sample is added to 5 mL of the dispersion liquid, and dispersed for 1 minute using an ultrasonic disperser. Then, 25 mL of the electrolyte is added, and further dispersed for 1 minute using an ultrasonic disperser to prepare a sample dispersion liquid. Measurement conditions: The sample dispersion was added to 100 mL of the electrolyte so that the particle size of 30,000 particles could be measured in 20 seconds. 30,000 particles were measured, and the volume median particle size (D 50 ) is required.

[0075] [Evaluation method] [Low temperature fixability and hot offset resistance with belt fixing unit] Toner was filled into a printer "Microline (registered trademark) 5400" (manufactured by Oki Data Corporation) that had been modified to be able to take unfixed images, and an unfixed image (unfixed image: a printed matter that has been transferred and has not yet passed through the fixing roll) of a solid image of 2 cm square was printed on a printing medium "J paper A4 size, high-quality paper" (manufactured by Fuji Xerox Co., Ltd.) Using an external fixing device modified from an NEC Corporation 45-sheet monochrome printer, MultiWriter 5500 (model number: PR-L5500), the rotation speed of the fixing roll was adjusted at a speed equivalent to a 30-sheet machine, and the temperature of the fixing roll was raised from 100°C to 230°C in 5°C increments to fix the unfixed image at each temperature, thereby obtaining a fixed image. The printed unfixed image was passed through an external fixing device, and the images obtained at each fixing temperature were visually observed to confirm the presence or absence of hot offset. When hot offset occurs, toner adheres to the fixing roll, resulting in a phenomenon in which the toner adheres to areas of the print medium where no image is formed (this state is deemed to have occurred). The temperature 5°C lower than the lowest fixing temperature at which hot offset occurs was used as an index of hot offset resistance. The higher the value, the better the hot offset resistance. The images obtained at each fixing temperature were rubbed five times with a sand eraser "ER-502R" (manufactured by Lion Office Products Co., Ltd.) with a load of 400g, and the image density before and after rubbing was measured using an image densitometer "Gretag SPM50" (manufactured by Gretag Macbeth Co., Ltd.). The temperature at which the image density ratio before and after rubbing ([image density after rubbing / image density before rubbing] x 100) first exceeded 90% was taken as the minimum fixing temperature, and was used as an index of low-temperature fixability. The smaller the value, the better the low-temperature fixability.

[0076] [Low temperature fixability with roller fixing device, hot offset resistance] Toner was filled into a printer "Microline (registered trademark) 5400" (manufactured by OKI Data Corporation) that had been modified to be able to take unfixed images, and an unfixed image of a 2 cm square solid image (unfixed image: a printed matter that has been transferred and has not yet passed through the fixing roll) was printed on a printing medium "J paper A4 size, high-quality paper" (manufactured by Fuji Xerox Co., Ltd.) Using an external fixing device modified from "OKI MICROLINE 3010" (manufactured by OKI Data Corporation), the rotation speed of the fixing roll was adjusted at a speed equivalent to a 30-sheet machine, and the temperature of the fixing roll was raised from 100°C to 230°C in increments of 5°C, and the unfixed image was fixed at each temperature to obtain a fixed image. The printed unfixed image was passed through an external fixing device, and the images obtained at each fixing temperature were visually observed to confirm the presence or absence of hot offset. When hot offset occurs, toner adheres to the fixing roll, resulting in a phenomenon in which the toner adheres to areas of the print medium where no image is formed (this state is deemed to have occurred). The temperature 5°C lower than the lowest fixing temperature at which hot offset occurs was used as an index of hot offset resistance. The higher the value, the better the hot offset resistance. The images obtained at each fixing temperature were rubbed five times with a sand eraser "ER-502R" (manufactured by Lion Office Products Co., Ltd.) with a load of 400g, and the image density before and after rubbing was measured using an image densitometer "Gretag SPM50" (manufactured by Gretag Macbeth Co., Ltd.). The temperature at which the image density ratio before and after rubbing ([image density after rubbing / image density before rubbing] x 100) first exceeded 90% was taken as the minimum fixing temperature, and was used as an index of low-temperature fixability. The smaller the value, the better the low-temperature fixability.

[0077] [Storability] 4 g of toner was placed in a 220 mL container (diameter approximately 3 cm) and left in a high temperature and high humidity environment (temperature 55°C, relative humidity 85%) for 60 hours. After that, the degree of toner aggregation was visually observed every 12 hours, and the heat resistance storage stability was evaluated according to the following evaluation criteria. (Evaluation Criteria) A + No aggregation was observed even after 84 hours. A: No aggregation was observed even at 72 hours, but aggregation was observed at 84 hours. B: No aggregation is observed even at 60 hours, but aggregation is observed at 72 hours. C: Aggregation is observed at 60 hours.

[0078] [Durability] The toner was loaded into a laser printer "Page Presto N-4" (Casio Computer Co., Ltd., fixing: contact fixing method, development: non-magnetic one-component development method, development roll diameter: 2.3 cm), and a durable continuous print was performed with a diagonal stripe pattern with an area ratio of 5.5% under conditions of a temperature of 32°C and a relative humidity of 85%. A solid image was printed every 500 sheets during the print, and the image was checked for streaks. When streaks on the image caused by the toner fusing and adhering to the development roll were visually observed, printing was stopped, and durability was evaluated according to the following evaluation criteria based on the number of prints up to that point. The results are shown in the table. Continuous printing was performed up to a maximum of 6,000 sheets. The higher the number of prints, the better the durability of the toner. [Evaluation Criteria] A ++ : Number of prints: 6,000 A + : The number of printed sheets is between 5,000 and 6,000 sheets A: The number of printed sheets is between 4,000 and 5,000. B: The number of printed sheets is between 3,000 and 4,000. C: The number of printed sheets is less than 3,000.

[0079] [Resin manufacturing] Production example A1 (resin A-1) The inside of a 10L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple was replaced with nitrogen, and 1,413g of propylene oxide (2.2) adduct of bisphenol A, 4,156g of ethylene oxide (2.2) adduct of bisphenol A, 2,430g of terephthalic acid, 374g of silicone "X-22-170BX" (manufactured by Shin-Etsu Chemical Co., Ltd.), and 40g of tin (II) di(2-ethylhexanoate) were added, and the mixture was heated to 235°C while stirring under a nitrogen atmosphere and maintained at 235°C for 6 hours. The pressure in the flask was then reduced, and the reaction was continued at 8kPa until the desired softening point, to obtain Resin A-1. The physical properties are shown in Table 1.

[0080] Production example A2~A3, A5 [Resin A-2~A-3, A-5] Resins A-2 to A-3 and A-5 were obtained in the same manner as in Production Example A1, except that the raw material compositions were changed as shown in Table 1. The physical properties are shown in Table 1.

[0081] Manufacturing example A4 [Resin A-4] The inside of a 10L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple was replaced with nitrogen, and 2,758g of 1,2-propanediol, 5,242g of terephthalic acid, 343g of silicone "X-22-170BX" (manufactured by Shin-Etsu Chemical Co., Ltd.), and 40g of tin(II) di(2-ethylhexanoate) were added, and the temperature was raised stepwise from 180°C to 220°C over 6 hours while stirring under a nitrogen atmosphere. The reaction was then continued at 8kPa until the desired softening point was obtained, yielding Resin A-4. The physical properties are shown in Table 1.

[0082] Manufacturing example A6 [Resin A-6] The inside of a 10 L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple was replaced with nitrogen, and 2,890 g of a propylene oxide (2.2) adduct of bisphenol A, 2,684 g of an ethylene oxide (2.2) adduct of bisphenol A, 1,563 g of terephthalic acid, 210 g of dodecenyl succinic anhydride, 374 g of silicone "X-22-170BX" (manufactured by Shin-Etsu Chemical Co., Ltd.), and 24 g of tin (II) di(2-ethylhexanoate) were placed in the flask, and the mixture was heated to 235°C with stirring under a nitrogen atmosphere and maintained at 235°C for 6 hours. The pressure in the flask was then reduced and maintained at 8 kPa for 1 hour. After that, the pressure was returned to atmospheric pressure, and the mixture was cooled to 220°C, and 653 g of trimellitic anhydride was added and reacted at 220°C for 0.5 hours. Then, the pressure in the flask was reduced, and the reaction was continued at 20 kPa until the desired softening point was reached, yielding Resin A-6. The physical properties are shown in Table 1.

[0083] Manufacturing example A81 [Resin A-81] The inside of a 10L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple was replaced with nitrogen, and 5,091g of L-lactide, 2,182g of D-lactide, and 727g of bis(2-hydroxypropyl) terephthalate were added, and the internal temperature was gradually raised to perform dehydration treatment under reduced pressure conditions. Next, the temperature was further raised under nitrogen purging, and after visually confirming that the system was homogenized, 24g of di(2-ethylhexanoate)tin(II) was added to the system to perform a polymerization reaction. At this time, the internal temperature of the system was controlled so as not to exceed 190°C. After 2 hours of reaction time, the system was switched back to the outflow line, and unreacted lactide was removed under reduced pressure conditions to complete the polymerization reaction and obtain a resin oligomer. Then, 5,882g of resin oligomer and 588g of silicone "X-22-160AS" (manufactured by Shin-Etsu Chemical Co., Ltd.) were added to the flask, and the internal temperature was gradually raised. After confirming that the system was homogenized, dehydration treatment was performed under reduced pressure. The temperature was then further increased, and 24 g of tin(II) di(2-ethylhexanoate) was added to the system at 170°C, after which 529 g of isophorone diisocyanate was gradually added as an elongation agent to carry out an elongation reaction, yielding Resin A-81. The physical properties are shown in Table 1.

[0084] Manufacturing Example A82 [Resin A-82] The inside of a 10L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple was replaced with nitrogen, 4,667g of L-lactide, 2,000g of D-lactide, and 1,333g of bis(2-hydroxypropyl) terephthalate were added, and the internal temperature was gradually raised to perform dehydration treatment under reduced pressure conditions. Next, the temperature was further raised under nitrogen purging, and after visually confirming that the system was homogenized, 24g of di(2-ethylhexanoate)tin(II) was added to the system to perform a polymerization reaction. At this time, the internal temperature of the system was controlled so as not to exceed 190°C. After 2 hours of reaction time, the system was switched back to the outflow line, and unreacted lactide was removed under reduced pressure conditions to complete the polymerization reaction and obtain a resin oligomer. Then, 6,140g of resin oligomer and 307g of silicone "X-22-160AS" (manufactured by Shin-Etsu Chemical Co., Ltd.) were added to the flask, and the internal temperature was gradually raised. After confirming that the system was homogenized, dehydration treatment was performed under reduced pressure. The temperature was then further increased, and 24 g of tin(II) di(2-ethylhexanoate) was added to the system at 170°C. 553 g of isophorone diisocyanate was then gradually added as an elongation agent to carry out an elongation reaction, yielding resin A-82. The physical properties are shown in Table 1.

[0085] Manufacturing example A83 [Resin A-83] The inside of a 10L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple was replaced with nitrogen, and 1,413g of propylene oxide (2.2) adduct of bisphenol A, 4,156g of ethylene oxide (2.2) adduct of bisphenol A, 2,430g of terephthalic acid, 374g of silicone "KF96-100cs" (manufactured by Shin-Etsu Chemical Co., Ltd.), and 40g of tin (II) di(2-ethylhexanoate) were added, and the mixture was heated to 235°C while stirring under a nitrogen atmosphere. After maintaining the temperature at 235°C for 6 hours, the pressure in the flask was reduced, and the reaction was continued at 8kPa until the desired softening point, and resin A-83 was obtained. The physical properties are shown in Table 1.

[0086] [Table 1-1]

[0087] [Table 1-2]

[0088] In the table, the various silicones used have the following configurations: X-22-170BX: Modified silicone oil "X-22-170BX" (a silicone having a carbinol group at one end [the above-mentioned silicone (a) (only one end is a group represented by formula (2a), and the group is the substituent 2a-1)]), kinematic viscosity (25°C) 40 mm 2 / s, number average molecular weight Mn 1,900, weight average molecular weight Mw 3,500, functional group equivalent 20g / mol, manufactured by Shin-Etsu Chemical Co., Ltd.)

[0089] KF-6001: Modified silicone oil "KF-6001" (a silicone having carbinol groups at both ends [the above-mentioned silicone (a) (both ends are groups represented by formula (2a), and the groups are the substituents 2a-1)], kinematic viscosity (25°C) 45 mm 2 / s, number average molecular weight Mn 1,800, weight average molecular weight Mw 2,700, functional group equivalent 900g / mol, manufactured by Shin-Etsu Chemical Co., Ltd.)

[0090] X-22-160AS: Modified silicone oil "X-22-160AS" (modified silicone having carbinol groups at both ends [the above-mentioned modified silicone (a) (both ends are groups represented by formula (2a), and the groups are the substituents 2a-1)], kinematic viscosity (25°C) 35 mm 2 / s, number average molecular weight Mn 1,000, weight average molecular weight Mw 1,400, functional group equivalent 470g / mol, manufactured by Shin-Etsu Chemical Co., Ltd.)

[0091] KF96-100cs: Silicone oil "KF96-100cs" (Silicone oil, dynamic viscosity (25℃) 100mm 2 / s, manufactured by Shin-Etsu Chemical Co., Ltd.)

[0092] Manufacturing example A21 [Resin A-21] The inside of a 10L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple was replaced with nitrogen, and 1,413g of propylene oxide (2.2) adduct of bisphenol A, 4,156g of ethylene oxide (2.2) adduct of bisphenol A, 2,430g of terephthalic acid, 374g of silicone "X-22-173BX" (manufactured by Shin-Etsu Chemical Co., Ltd.), and 40g of tin (II) di(2-ethylhexanoate) were added, and the mixture was heated to 235°C while stirring under a nitrogen atmosphere and maintained at 235°C for 6 hours. The pressure in the flask was then reduced, and the reaction was continued at 8kPa until the desired softening point, obtaining resin A-21. The physical properties are shown in Table 2.

[0093] Manufacturing example A22~A23, A25~A28 [Resin A-22~A-23, A-25~A-28] Resins A-22 to A-23 and A-25 to A-28 were obtained in the same manner as in Production Example A21, except that the raw material composition was changed as shown in Table 2. The physical properties are shown in Table 2.

[0094] Manufacturing example A24 [Resin A-24] The inside of a 10L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple was replaced with nitrogen, and 2,758g of 1,2-propanediol, 5,242g of terephthalic acid, 343g of silicone "X-22-173BX" (manufactured by Shin-Etsu Chemical Co., Ltd.), and 40g of tin(II) di(2-ethylhexanoate) were added, and the temperature was raised stepwise from 180°C to 220°C over 6 hours while stirring under a nitrogen atmosphere. The reaction was then continued at 8kPa until the desired softening point was obtained, yielding resin A-24. The physical properties are shown in Table 2.

[0095] Manufacturing example A29 [Resin A-29] The inside of a 10 L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple was replaced with nitrogen, and 2,890 g of a propylene oxide (2.2) adduct of bisphenol A, 2,684 g of an ethylene oxide (2.2) adduct of bisphenol A, 1,563 g of terephthalic acid, 210 g of dodecenyl succinic anhydride, 374 g of silicone "X-22-173BX" (manufactured by Shin-Etsu Chemical Co., Ltd.), and 24 g of tin (II) di(2-ethylhexanoate) were placed in the flask, and the mixture was heated to 235°C with stirring under a nitrogen atmosphere and maintained at 235°C for 6 hours. The pressure in the flask was then reduced and maintained at 8 kPa for 1 hour. After that, the pressure was returned to atmospheric pressure, and the mixture was cooled to 220°C, and 653 g of trimellitic anhydride was added and reacted at 220°C for 0.5 hours. Then, the pressure in the flask was reduced, and the reaction was continued at 20 kPa until the desired softening point was reached, yielding Resin A-29. The physical properties are shown in Table 2.

[0096] [Table 2-1]

[0097] [Table 2-2]

[0098] In the table, the various modified silicones used have the following structures. X-22-173BX: Modified silicone oil "X-22-173BX" (modified silicone having an epoxy group at one end [the above-mentioned modified silicone (b) (only one end is a group represented by formula (2b), and the group is the substituent 2b-1)], kinematic viscosity (25°C) 30 mm 2 / s, number average molecular weight Mn 1,900, weight average molecular weight Mw 3,300, functional group equivalent 2,500g / mol, manufactured by Shin-Etsu Chemical Co., Ltd.)

[0099] X-22-163C: Modified silicone oil "X-22-163C" (modified silicone having epoxy groups at both ends [the above-mentioned modified silicone (b) (both ends are groups represented by formula (2b), and the groups are the substituents 2b-1)], kinematic viscosity (25°C) 120 mm2 / s, number average molecular weight Mn 3,000, weight average molecular weight Mw 8,000, functional group equivalent 2,700g / mol, manufactured by Shin-Etsu Chemical Co., Ltd.)

[0100] BY16-750: Modified silicone oil "BY16-750" (modified silicone having carboxyl groups at both ends [the above-mentioned modified silicone (c) (both ends are groups represented by formula (2c)]), kinematic viscosity (25°C) 170 mm 2 / s, number average molecular weight Mn 1,400, weight average molecular weight Mw 2,200, functional group equivalent 750g / mol, manufactured by Dow Corning Toray Co., Ltd.)

[0101] X-22-3710: Modified silicone oil "X-22-3710" (modified silicone having a carboxyl group at one end [the above-mentioned modified silicone (c) (one end is a group represented by formula (2c)]), kinematic viscosity (25°C) 60 mm 2 / s, number average molecular weight Mn 2,600, weight average molecular weight Mw 5,800, functional group equivalent 1,450g / mol, manufactured by Shin-Etsu Chemical Co., Ltd.)

[0102] X-22-162C: Modified silicone oil "X-22-162C" (modified silicone having carboxyl groups at both ends [the above-mentioned modified silicone (c) (one end is a group represented by formula (2c), and the group is the substituent 2c-1)], kinematic viscosity (25°C) 220 mm 2 / s, number average molecular weight Mn 2,600, weight average molecular weight Mw 7,800, functional group equivalent 2,300g / mol, manufactured by Shin-Etsu Chemical Co., Ltd.)

[0103] Manufacturing example B1 (resin B-1) The inside of a 10L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple was replaced with nitrogen, and 2,890g of propylene oxide (2.2) adduct of bisphenol A, 2,684g of ethylene oxide (2.2) adduct of bisphenol A, 1,563g of terephthalic acid, 210g of dodecenyl succinic anhydride, and 24g of di(2-ethylhexanoate) tin (II) were added, and the mixture was heated to 235°C under a nitrogen atmosphere while stirring. After maintaining the mixture at 235°C for 6 hours, the pressure in the flask was reduced and maintained at 8kPa for 1 hour. After that, the mixture was returned to atmospheric pressure, cooled to 220°C, 653g of trimellitic anhydride was added, and the mixture was reacted at 220°C for 0.5 hours. After that, the pressure in the flask was reduced and the mixture was reacted at 20kPa until the desired softening point was reached, and resin B-1 was obtained. The physical properties are shown in Table 3.

[0104] Manufacturing example B2 (resin B-2) The inside of a 10L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple was replaced with nitrogen, and 1,413g of propylene oxide (2.2) adduct of bisphenol A, 4,156g of ethylene oxide (2.2) adduct of bisphenol A, 2,430g of terephthalic acid, and 40g of tin (II) di(2-ethylhexanoate) were added, and the mixture was heated to 235°C while stirring under a nitrogen atmosphere. After maintaining the temperature at 235°C for 6 hours, the pressure in the flask was reduced, and the reaction was continued at 8kPa until the desired softening point, and resin B-2 was obtained. The physical properties are shown in Table 3.

[0105] [Table 3]

[0106] [Toner manufacturing] Example 1 [Toner 1] 65 parts by weight of resin A-1, 35 parts by weight of resin B-1, 1 part by weight of negatively charged charge control agent "LR-147" (manufactured by Nippon Carlit Co., Ltd.), and 1 part by weight of copper phthalocyanine pigment "ECB-301" (manufactured by Dainichiseika Color & Chemicals Mfg. Co., Ltd., CI Pigment Blue 15:3) were mixed for 1 minute using a Henschel mixer. The resulting raw material mixture was mixed in a twin-screw extruder "PCM-30" (manufactured by Ikegai Corporation, shaft diameter 29 mm, shaft cross-sectional area 7.06 cm 2 The mixture was melt-kneaded using a barrel at a mixture supply rate of 8 kg / h, a barrel temperature of 100° C., and a rotation speed of 200 r / min (circumferential speed of 0.30 m / sec). The obtained molten kneaded material was crushed and classified in a crushing classifier "IDS-2 / DS2 type" (manufactured by Nippon Pneumatic Mfg. Co., Ltd.) under the conditions of a kneaded material supply rate of 2.5 kg / h, upper damper 30°, CC ring 30 mm, OE ring 20 mm, louver 1.5 mm, and collision plate distance 30 mm, and the volume median particle size (D 50 ) yielded 5.5 μm toner particles.

[0107] 100 parts by mass of toner particles, 0.5 parts by mass of hydrophobic silica "R972" (manufactured by Nippon Aerosil Co., Ltd., hydrophobic treatment agent "DMDS", average particle size: 16 nm) as an external additive, and 1.0 part by mass of hydrophobic silica "RY-50" (manufactured by Nippon Aerosil Co., Ltd., hydrophobic treatment agent: silicone oil, average particle size: 40 nm) were mixed in a Henschel mixer at 3,000 r / min (circumferential speed 32 m / sec) for 3 minutes to obtain toner 1. In Example 1, the low temperature fixing property and hot offset resistance in a belt fixing device were evaluated. The results of various evaluations are shown in Table 4.

[0108] Examples 2 to 6, Comparative Examples 1 to 4 (Toners 2 to 6, 81 to 84) Toners 2 to 6 and 81 to 84 were obtained in the same manner as in Example 1, except that the resin was changed as shown in Table 4. In Examples 2 to 6 and Comparative Examples 1 to 4, toners 2 to 6 and 81 to 84 were evaluated for low temperature fixability and hot offset resistance in a belt fixing device. The results of the various evaluations are shown in Table 4.

[0109] Example 11, Comparative Examples 11-12 (Toners 11-13) The volume median particle size of toner particles (D 50) were changed as shown in Table 4, the same procedure as in Example 1 was followed to obtain toners 11 to 13. In Example 11 and Comparative Examples 11 to 12, the toners 11 to 13 were evaluated for low temperature fixability in a belt fixing device and hot offset resistance. The results of the various evaluations are shown in Table 4.

[0110] Reference Examples 1 to 5 (Toners 1, 11 to 13, 81) In Reference Examples 1 to 5, the low temperature fixability in a roller fixing device and the hot offset resistance were evaluated for each of Toners 1, 11 to 13, and 81. The results of the various evaluations are shown in Table 4.

[0111] [Table 4-1]

[0112] [Table 4-2]

[0113] [Table 4-3]

[0114] [Table 4-4]

[0115] From the results of Examples 1 to 6 and 11 and Comparative Examples 1 to 4 and 11 to 12, it is clear that the present invention provides a toner excellent in low-temperature fixing property, hot offset resistance and storage stability.

[0116] Example 21 [Toner 21] 65 parts by weight of resin A-21, 35 parts by weight of resin B-1, 1 part by weight of negatively charged charge control agent "LR-147" (manufactured by Nippon Carlit Co., Ltd.), and 1 part by weight of copper phthalocyanine pigment "ECB-301" (manufactured by Dainichiseika Color & Chemicals Mfg. Co., Ltd.) were mixed for 1 minute using a Henschel mixer, and then melt-kneaded under the conditions shown below. The resulting raw material mixture was mixed in a twin-screw extruder "PCM-30" (manufactured by Ikegai Corporation, shaft diameter 29 mm, shaft cross-sectional area 7.06 cm 2 The mixture was melt-kneaded using a barrel at a mixture supply rate of 8 kg / h, a barrel temperature of 100° C., and a rotation speed of 200 r / min (circumferential speed of 0.30 m / sec). The obtained molten mixture was crushed and classified in a crusher / classifier "IDS-2 / DS2 type" (manufactured by Nippon Pneumatic Mfg. Co., Ltd.) under the conditions of a mixture supply rate of 2.5 kg / h, upper damper 30°, CC ring 30 mm, OE ring 20 mm, louver 1.5 mm, and collision plate distance 30 mm, and the volume median particle size (D 50 ) yielded 5.5 μm toner particles. 100 parts by mass of the obtained toner particles, 0.5 parts by mass of hydrophobic silica "R972" (manufactured by Nippon Aerosil Co., Ltd., hydrophobic treatment agent: DMDS, average particle size: 16 nm) as an external additive, and 1.0 part by mass of hydrophobic silica "RY-50" (manufactured by Nippon Aerosil Co., Ltd., hydrophobic treatment agent: silicone oil, average particle size: 40 nm) were mixed in a Henschel mixer at 3000 r / min (circumferential speed: 32 m / sec) for 3 minutes to obtain toner 21. Toner 21 was evaluated for low temperature fixability and hot offset resistance in a belt fixing device. The results of various evaluations are shown in Table 5.

[0117] Examples 22 to 29, Comparative Examples 21 to 22 [Toners 22 to 29, 91 to 92] Toners 22 to 29 and 91 to 92 were obtained in the same manner as in Example 21, except that the resin was changed as shown in Table 5. The low-temperature fixability and hot offset resistance of toners 22 to 29 and 91 to 92 were evaluated using a belt fixing device. The results of the various evaluations are shown in Table 5.

[0118] [Table 5-1]

[0119] [Table 5-2]

[0120] From the results of Examples 21 to 29 and Comparative Examples 21 to 22, it is clear that the present invention provides a toner excellent in low-temperature fixing property, hot offset resistance and durability.

Claims

1. 1. A toner for electrophotography comprising toner particles, the toner particles contain, as a binder resin, a resin (A) which is a reaction product of an alcohol component containing a divalent or higher alcohol, a carboxylic acid component containing a divalent or higher carboxylic acid compound, and a modified silicone having a hydroxy group, a carboxy group, or an epoxy group at one or both ends (however, when the modified silicone has a hydroxy group at one or both ends, the number average molecular weight of the resin (A) is 1,000 or more and 10,000 or less); the carboxylic acid component contains an aromatic dicarboxylic acid compound, and the content of the aromatic dicarboxylic acid compound in the carboxylic acid component is 50 mol % or more; The volume median particle size (D 50 ) is 6.5 μm or less, An electrophotographic toner used in an electrophotographic apparatus using a belt fixing system or a free belt nip fixing system in a fixing device.

2. The modified silicone has the formula (1): 【Chemistry 1】 2. The toner for electrophotography according to claim 1, comprising a modified silicone represented by the following formula: (in which R is independently a hydrocarbon group having from 1 to 6 carbon atoms, R' is independently an alkylene group having from 1 to 10 carbon atoms, R'' is independently a hydrocarbon group having from 1 to 10 carbon atoms, X is independently a hydroxy group, a hydroxyalkyloxy group, a carboxy group, a carboxyalkyloxy group, an epoxy group, a glycidyl group, a glycidyloxy group, or an alicyclic epoxy group, s is an integer of 1 to 3, t is an integer of 0 to 3, and n is an integer of 5 to 300).

3. 3. The toner for electrophotography according to claim 1, wherein the modified silicone has a hydroxyl group at one or both ends.

4. 3. The toner for electrophotography according to claim 1, wherein the modified silicone has an epoxy group at one end or at both ends.

5. 3. The toner for electrophotography according to claim 1, wherein the modified silicone has a carboxyl group at one end or at both ends.

6. 6. The toner for electrophotography according to claim 1, wherein a mass ratio of the modified silicone is 1 mass % or more and 7 mass % or less with respect to a total amount of the alcohol component, the carboxylic acid component, and the modified silicone.

7. 7. The toner for electrophotography according to claim 1, wherein the content of the wax is from 0 part by mass to 1 part by mass with respect to 100 parts by mass of the total amount of the binder resin.

Citation Information

Patent Citations

  • Composite polyester resin

    JP2002012657A

  • Resin for toner, toner, developer, and image forming apparatus

    JP2012242448A

  • Toner binder resin

    JP2020063348A

  • Toner binder resin

    JP2020063412A

  • White toner

    JP2020148992A